2015
DOI: 10.1097/sap.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

The Oncologic Safety of Breast Fat Grafting and Contradictions Between Basic Science and Clinical Studies

Abstract: Fat grafting is increasingly popular and is becoming a common practice in plastic surgery for postmastectomy breast reconstruction and aesthetic breast augmentation; however, concerns over the oncologic safety remains a controversial and hot topic among scientists and surgeons. Basic science and laboratory research repeatedly show a potentially dangerous effect of adipose-derived stem cells on breast cancer cells; however, clinical research, although limited, continually fails to show an increase in breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The number of transplanted stem cells is also believed to play an important role in the observed discordances. However, the crucial cut-off value cannot be determined with the existing evidence [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of transplanted stem cells is also believed to play an important role in the observed discordances. However, the crucial cut-off value cannot be determined with the existing evidence [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Future research should be oriented to both preclinical and clinical studies in order to elucidate all the contradictory points in this field [23]. Another interesting perspective would be the simultaneous use of ASCs as carriers of chemotherapeutic drugs with locoregional action [22].…”
Section: Discussionmentioning
confidence: 99%
“…5 A generalized contradiction between basic science studies and clinical studies further adds to the uncertainty regarding fat grafting and its potential effect on oncogenic potential, with basic science studies demonstrating potential mechanisms of promoting tumor growth and clinical studies suggesting there is no increased oncologic risk. 6 We commend the authors for developing a scientific study to complement their clinical observation regarding the potential link between fat grafting and the recurrence of osteosarcoma. 5 Previous studies suggest that localized, primary osteosarcomas typically have a local recurrence rate of 30 to 50 percent.…”
mentioning
confidence: 99%
“…Recently, concerns have been raised over the risk of the stem‐cell content of adipose derivatives provoking cancer recurrence. This has been investigated primarily in patients with prior breast cancer; however, although several murine models have demonstrated that adipose progenitor cells may stimulate local and metastatic breast cancer, definitive proof of an increased risk to humans has not been demonstrated and larger, prospective, controlled studies are recommended [4].…”
mentioning
confidence: 99%